2017
DOI: 10.1016/j.tox.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Brominated and organophosphate flame retardants target different neurodevelopmental stages, characterized with embryonic neural stem cells and neuronotypic PC12 cells

Abstract: In addition to their activity as endocrine disruptors, brominated and organophosphate flame retardants are suspected to be developmental neurotoxicants, although identifying their specific mechanisms for that activity has been elusive. In the current study, we evaluated the effects of several flame retardants on neurodifferentiation using two in vitro models that assess distinct “decision nodes” in neural cell development: embryonic rat neural stem cells (NSCs), which evaluate the origination of neurons and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 42 publications
0
25
0
1
Order By: Relevance
“…Considering that organophosphate compounds generally inhibit the AChE enzyme that breaks down the neurotransmitter acetylcholine (De Jong and Benschop, 1988;Taylor, 2001), it is not surprising to find neurogenesis related genes in a responsive group. It has been reported that the development of neurons was the targeted biological process in developing zebrafish embryo and rat PC12 cells when exposed to chlorpyrifos-oxon (Jacobson et al, 2010) and to tris (1,3-dichloro-2-propyl) phosphate (Slotkin et al, 2017).…”
Section: Gene Expression Change In Response To Parathionmentioning
confidence: 99%
“…Considering that organophosphate compounds generally inhibit the AChE enzyme that breaks down the neurotransmitter acetylcholine (De Jong and Benschop, 1988;Taylor, 2001), it is not surprising to find neurogenesis related genes in a responsive group. It has been reported that the development of neurons was the targeted biological process in developing zebrafish embryo and rat PC12 cells when exposed to chlorpyrifos-oxon (Jacobson et al, 2010) and to tris (1,3-dichloro-2-propyl) phosphate (Slotkin et al, 2017).…”
Section: Gene Expression Change In Response To Parathionmentioning
confidence: 99%
“…Results of previous studies have indicated that TDCPP can cause neurotoxicity, developmental toxicity, endocrine disruption and hepatotoxicity (Li et al, 2015;Slotkin et al, 2017). Also, TDCPP exposure caused different toxicity in zebrafish, including cell cycle arrest, DNA damage and apoptosis (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While several of the 15 FRs that we screened have been previously studied in other systems, including rodents (Cope et al, 2015; EFSA, 2011; Moser et al, 2015; Nakajima et al, 2009; National Toxicology Program, 1991; Viberg and Eriksson, 2011) and other alternative models (Alzualde et al, 2018; Bailey and Levin, 2015; Cano-Sancho et al, 2017; Glazer et al, 2018; Oliveri et al, 2015; Slotkin et al, 2017; Usenko et al, 2016), only a handful of studies have performed direct multi-FR comparisons as provided here. Fourteen of the 15 unique FRs tested in this screen have been previously studied in developing zebrafish, nematodes, and in vitro cell-based (mouse embryonic stem cell, human neural stem cell, and rat neuron) systems with some FRs showing developmental toxicity or DNT.…”
Section: Resultsmentioning
confidence: 99%